PENGEMBANGAN APLIKASI BEMPI (BELAJAR MENULIS PUISI) UNTUK PEMBELAJARAN MANDIRI MENULIS PUISI DI KELAS V SD - Nailul Amaniah, Ina; Djuanda, Dadan; Dwija Iswara, Prana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low ability of grade V elementary school students in writing poetry independently. Learners have difficulty in finding ideas, choosing diction/majas, difficulty expressing feelings and the lack of interesting and appropriate learning media. The purpose of this research is to develop the BEMPI (Learning to Write Poetry) application as an independent learning media that can improve students' poetry writing skills, determine the feasibility of the application, and determine user responses to the application. The research method uses the Design and Development (D&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of media experts, material experts, teachers, and fifth grade students of SD Negeri Sangkanmulya, Kuningan Regency. Data collection instruments were interviews and questionnaires. The results showed that the BEMPI application obtained a percentage of feasibility from media expert validation of 92.50% and from material expert validation of 88.75%, which was included in the “very feasible” category. The response of students and teachers to this application is also very positive, getting the results of the percentage of small group students 98.50% and large groups 95.25% and from the teacher's response 96.25% which is classified as “very good”. Thus, the BEMPI application is proven to be feasible to be used as a medium for independent learning to write poetry in elementary schools and can stay away from poetry.